Brand Personality Scale: How Do Indian Consumers Interpret The Personality Dimensions? - Khandai, Sujata; Agrawal, Bhawna; Gulla, Anju (Asian Academy of Management (AAM), 2015)
With brands assuming an important and all-encompassing position in the marketplace today and with the excessive proliferation of me-too products, marketers have recognised the need to create a distinct personality for a brand so that it stands adequately differentiated in the market. This study tests the applicability of Jennifer Aaker's (1997) brand personality scale in the Indian context and identifies significant similarities and differences in brand personality perceptions. Focus groups were used to identify the product categories and brands to be used in the study. Thereafter, Primary Component Analysis was used to isolate the factors (personality dimensions) for each brand. Data were collected using self-administered questionnaires. The study used just four product categories. Further studies could increase the number of product categories and brands to widen the scope of study.